Derivation of the Capital Asset Pricing Model without Normality or Quadratic Preference: A Note - KWON, YOUNG K. (Journal of Finance, 1985)
ABSTRACT Derivation of the capital asset pricing model requires various assumptions including normality or quadratic preference. The objective of this note is to show that the normality or quadratic preference assumption can be replaced by the fair game condition that assets' residual returns have zero mean conditional upon the return of the market portfolio.